El don como principio crítico democratizador. Una reflexión sobre la crisis de la democracia - Caviglia, Alessandro (2023)
The text deals with the crisis of democracy and examines the possibilities of the theory of reciprocity to deal with it. The theory of reciprocity has one foot in the philosophical work of Kant. We first present the relationship between crisis and criticism present in his work, and then move on to the rearticulation of criticism in the theory of reciprocity. With this, democratization is presented to deal with the crisis. Since networks of trust and the gift have a central place in such terrain, we will examine the capacities that such elements offer to face the crisis.